2016
DOI: 10.1007/s00167-016-4009-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of increased flexion gap after total knee arthroplasty. Can controlled gap imbalance improve knee flexion?

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…These findings are supported by a recent study by Ismailidis et al. ( 2017 ) that found a positive effect on postoperative flexion and patient satisfaction in knees where the flexion gap exceeded the extension gap by 2.5 mm. Furthermore, Tsukiyama et al.…”
Section: Discussionsupporting
confidence: 83%
“…These findings are supported by a recent study by Ismailidis et al. ( 2017 ) that found a positive effect on postoperative flexion and patient satisfaction in knees where the flexion gap exceeded the extension gap by 2.5 mm. Furthermore, Tsukiyama et al.…”
Section: Discussionsupporting
confidence: 83%
“…Some previous studies reported AP translation of 5–10 mm was related to similar or better patients’ clinical outcomes. 15,33 However, in an outpatient clinic, some patients with no excessive AP translation less than 10 mm complain about ascending or descending stairs and walking downhill. Mochizuki et al 22 demonstrated that more than 7 mm of mid-flexion AP laxity can cause feeling of instability.…”
Section: Discussionmentioning
confidence: 99%
“…As flexion gap increases by cutting PCL, surgeons have been concerned about the flexion gap growing too large in PS-TKA [4]. Flexion gap has been reported to affect postoperative range of motion and clinical outcomes [13][14][15]. Therefore, adjusting the flexion gap is a crucial component of PS-TKA [16].…”
Section: Resultsmentioning
confidence: 99%